2016
DOI: 10.1002/aenm.201601130
|View full text |Cite
|
Sign up to set email alerts
|

Heterojunction‐Depleted Lead‐Free Perovskite Solar Cells with Coarse‐Grained B‐γ‐CsSnI3 Thin Films

Abstract: Perovskite solar cells (PSCs) have been emerging as a breakthrough photovoltaic technology, holding unprecedented promise for low‐cost, high‐efficiency renewable electricity generation. However, potential toxicity associated with the state‐of‐the‐art lead‐containing PSCs has become a major concern. The past research in the development of lead‐free PSCs has met with mixed success. Herein, the promise of coarse‐grained B‐γ‐CsSnI3 perovskite thin films as light absorber for efficient lead‐free PSCs is demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
223
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 288 publications
(228 citation statements)
references
References 40 publications
5
223
0
Order By: Relevance
“…[48] It is also found that the crystallinity of Cs 2 AgBiBr 6 film is able to be improved, which is evidenced by the fact that the intensity of XRD diffraction peaks of Cs 2 AgBiBr 6 film increase as the postannealing temperature increases (Figure 3k). [49] We further test the photovoltaic performance of the Cs 2 AgBiBr 6 film prepared by the anti-solvent dropping method, and a series of inverted planar heterojunction PSCs with the structure of indium tin oxide (ITO)/Cu-NiO/Cs 2 AgBiBr 6 /C 60 /bathocuproine (BCP)/Ag are fabricated (Figure 3m). Moreover, the average grain sizes of the films are determined by analyzing the statistics of grain size in SEM images ( Figure S8).…”
Section: High-quality Cs 2 Agbibr 6 Double Perovskite Film For Lead-fmentioning
confidence: 99%
“…[48] It is also found that the crystallinity of Cs 2 AgBiBr 6 film is able to be improved, which is evidenced by the fact that the intensity of XRD diffraction peaks of Cs 2 AgBiBr 6 film increase as the postannealing temperature increases (Figure 3k). [49] We further test the photovoltaic performance of the Cs 2 AgBiBr 6 film prepared by the anti-solvent dropping method, and a series of inverted planar heterojunction PSCs with the structure of indium tin oxide (ITO)/Cu-NiO/Cs 2 AgBiBr 6 /C 60 /bathocuproine (BCP)/Ag are fabricated (Figure 3m). Moreover, the average grain sizes of the films are determined by analyzing the statistics of grain size in SEM images ( Figure S8).…”
Section: High-quality Cs 2 Agbibr 6 Double Perovskite Film For Lead-fmentioning
confidence: 99%
“…[12,13] In an attempt to improve the PCE, research efforts have been directed towards optimization of the tin-perovskite film morphology, tuning the film composition, use of a reducing agent, and modification of the device structure. [14][15][16][17][18][19][20][21] The main challenges for further improving the PCE lie in preventing the easy formation of Sn vacancies due to their small formation energy and the fast oxidation of divalent Sn 2+ into more stable Sn 4+ . This causes high levels of self-p-doping in Sn-based perovskite films, with consequent severe recombination losses for charge carriers.…”
Section: Doi: 101002/aenm201702019mentioning
confidence: 99%
“…Mixed-halide and mixed-cation perovskites have been investigated to address these issues. [23,[33][34][35][37][38][39][40] In addition, the easy oxidation of Sn and Ge from the +2 state to the +4 state due to their high energy 5s and 4s orbitals makes them less promising for application in stable and long-term PSCs. However, the device performance through this approach has fallen short of the Pb-based ones.…”
mentioning
confidence: 99%